From Field to Model: Determining EROSION 3D Model Parameters for the Emerging Biomass Plant Silphium perfoliatum L. to Predict Effects on Water Erosion Processes - Tobias Koch; Peter Aartsma; Detlef Deumlich; Peter Chifflard; Kerstin Panten (Agronomy)
The agricultural production of maize (Zea mays L.) increases the risk of water erosion. Perennial crops like cup plant (Silphium perfoliatum L.) offer a sustainable alternative to produce biomass for biogas plants. The assessment of soil conservation measures requires calibrated soil erosion models that spatially identify soil erosion processes. These support decision-making by farmers and policymakers. Input parameters for the physically based soil erosion model EROSION 3D for cup plant cultivation were established in a field study. Rainfall simulation experiments were conducted to determine the model input parameter’s skinfactor and surface roughness. The results showed a reduction of soil erosion and higher infiltration rates for cup plant resulting in higher skinfactors of 11.5 in June and 0.75 post-harvest (cup plant) compared to 1.2 in June and 0.21 post-harvest (maize). With the extended parameter catalogue of EROSION 3D for cup plant cultivation model simulations were conducted for a rainfall event in June (64 mm). The sediment budget would have been reduced by 92.6% through the growth of cup plant in comparison to conventionally grown maize. Perennial cup plant can, therefore, contribute to achieving the targets outlined in the European Green Deal by reducing soil erosion and enhancing soil health.